Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand - Kangrang, Punnatut; Thoni, Ryan J.; Mayden, Richard L.; Beamish, F. William H. (Zootaxa, 2016)
Garra fluviatilis is a new species described herein from the Kwai Noi, Mae Khlong basin, in the Thong Pha Phum District of Kanchanaburi Province in western Thailand. It is diagnosed by the following combination of morphological characters: well developed upper lip with unculiferous papillae, mottled pigmentation pattern, a pleated papilliferous fold at the junction of the anterolateral lobe and anteromedial fold on the lower lip, 4–5 anal scales, relatively deep body, keeled nape, and a laterally straight anterior margin of the anteromedial fold. Based on shared apomorphic morphological characters, we hypothesize that the new species is most closely related to G. spilota in nearby Myanmar.